Mounting of Biomaterials for Use in Ophthalmic Cell Therapies. Issue 11 (November 2017) - Harkin, Damien G.; Dunphy, Siobhan E.; Shadforth, Audra M. A.; Dawson, Rebecca A.; Walshe, Jennifer; Zakaria, Nadia
When used as scaffolds for cell therapies, biomaterials often present basic handling and logistical problems for scientists and surgeons alike. The quest for an appropriate mounting device for biomaterials is therefore a significant and common problem. In this review, we provide a detailed overview of the factors to consider when choosing an appropriate mounting device including those experienced during cell culture, quality assurance, and surgery. By way of example, we draw upon our combined experience in developing epithelial cell therapies for the treatment of eye diseases. We discuss commercially available options for achieving required goals and provide a detailed analysis of 4 experimental designs developed within our respective laboratories in Australia, the United Kingdom, and Belgium.